2016
DOI: 10.1101/068429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics and fate of beneficial mutations under lineage contamination by linked deleterious mutations

Abstract: Beneficial mutations drive adaptive evolution, yet their selective advantage does not ensure their fixation. Haldane's application of single-type branching process theory showed that genetic drift alone could cause the extinction of newly arising beneficial mutations with high probability. With linkage, deleterious mutations will affect the dynamics of beneficial mutations and might further increase their extinction probability. Here, we model the lineage dynamics of a newly arising beneficial mutation as a mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 78 publications
2
10
0
Order By: Relevance
“…As a result, the large population again enters the sequential fixation regime where clonal interference is absent. This effect has been recently shown by Pénisson et al (2017) when the beneficial and deleterious effects are nearly equal, and here we have provided a demonstration of the same in the limit…”
Section: Substitution Ratesupporting
confidence: 78%
See 2 more Smart Citations
“…As a result, the large population again enters the sequential fixation regime where clonal interference is absent. This effect has been recently shown by Pénisson et al (2017) when the beneficial and deleterious effects are nearly equal, and here we have provided a demonstration of the same in the limit…”
Section: Substitution Ratesupporting
confidence: 78%
“…Thus, when µ < λ, the fixation probability is 2s b (on replacing i by its average µ) and zero otherwise. For moderately sized deleterious effect, this transition has been observed, mainly numerically, in previous work (Johnson and Barton, 2002;Pénisson et al, 2017), while here we have shown it analytically using the explicit expression (13) for the fixation probability.…”
Section: Rate Of Adaptation In Asexualssupporting
confidence: 77%
See 1 more Smart Citation
“…One cluster of mutations in the polymerase subunit PA was associated with the subcellular localization of viral RdRp components, and two of these RdRp mutations conferred resistance to favipiravir in IAV-infected cells (Goldhill et al 2018). Nonetheless, under high concentrations of favipiravir, the Bank et al study observed no mutational escape, consistent with the idea that even in the presence of newly arising beneficial resistance mutations, the linked deleterious load under strong mutation pressure can be simply too great to enable significant net adaptation (Pénnison et al 2017), again emphasizing the potential advantage of such a genome-wide target size.…”
Section: Experimental Insights Into Mutational Meltdownmentioning
confidence: 73%
“…Also working in IAV, Ormond et al (2017) examined the combined effect of favipiravir with oseltamivir, a widely-used treatment with well-studied resistance mutations. A similar mutational meltdown outcome was observed, with the selective sweeps of oseltamivir-resistant mutations appearing to actually speed population decline, owing to the resulting hitchhiking of linked deleterious variants in the viral population (and see the related work of Pénnison et al 2017).…”
mentioning
confidence: 68%